The role of eviction in veterans' homelessness recidivism*. Issue 1 (2nd January 2017) - Cusack, Meagan; Montgomery, Ann Elizabeth
ABSTRACT: Eviction is one of the leading causes of homelessness in the U.S.A. Though permanent supportive housing (PSH) helps participants maintain housing, some still leave due to eviction. This study aimed to determine whether eviction is an important predictor of recidivism and time to return to homelessness for participants exiting PSH. The characteristics and post-exit service use of 2802 Veteran PSH participants were analyzed based on exit reason. A Cox proportional hazards survival analysis modeled risk factors for returning to homelessness within 360 days of exit. Compared with other exiters, evicted Veterans remained in the program for less time, were less likely to be receiving service-connected compensation, and used more services – particularly mental health and substance use services – following their exit, and those who returned to homelessness did so more quickly. Identifying participants who might benefit from more intensive services, project-based housing, or income supports may prevent evictions and subsequent returns to homelessness.